2018
DOI: 10.1016/bs.acr.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

VDAC Regulation: A Mitochondrial Target to Stop Cell Proliferation

Abstract: Cancer metabolism is emerging as a chemotherapeutic target. Enhanced glycolysis and suppression of mitochondrial metabolism characterize the Warburg phenotype in cancer cells. The flux of respiratory substrates, ADP, and Pi into mitochondria and the release of mitochondrial ATP to the cytosol occur through voltage-dependent anion channels (VDACs) located in the mitochondrial outer membrane. Catabolism of respiratory substrates in the Krebs cycle generates NADH and FADH2 that enter the electron transport chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 147 publications
(172 reference statements)
3
83
1
5
Order By: Relevance
“…The accumulation of rhodamine 123 confirmed that erastin significantly antagonized the drug-efflux function of ABCB1. Moreover, it has been reported that the safety of erastin in xenograft modes is acceptable (43,44). Inhibition of SLC7A11 by erastin also increased the sensitivity of cisplatin in cancer cells (19,45), suggesting the combination of erastin and chemotherapeutical reagents can be sufficient for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of rhodamine 123 confirmed that erastin significantly antagonized the drug-efflux function of ABCB1. Moreover, it has been reported that the safety of erastin in xenograft modes is acceptable (43,44). Inhibition of SLC7A11 by erastin also increased the sensitivity of cisplatin in cancer cells (19,45), suggesting the combination of erastin and chemotherapeutical reagents can be sufficient for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Kyoto encyclopedia of genes and genomes (KEGG) enrichment analysis discovered six signaling pathways (Table S2), i.e., cGMP-PKG signaling pathway, NOD-like receptor signaling pathway, calcium signaling pathway, cholesterol metabolism, necroptosis, and ferroptosis, which were influenced by SARS-CoV-2 S1 (Figure 4b). The up-regulation of VDAC1-3, three mitochondrial membrane porins involved in bioenergetic failure and cell apoptosis, [19][20] were attributable. In the presence of HEK-293T-hACE2 NPs, the imbalance of VDAC1-3 was corrected ( Figure 4c), and the number of changed proteins was reduced to thirty-one (Table S3), by which no signaling pathway was enriched by KEGG yet.…”
Section: Hek-293t Nps Prepared Using the Same Methods Had Comparablementioning
confidence: 99%
“…Although VDACs have been largely considered constitutively open, recent studies show that VDACs conductance capacity is inhibited by intracellular free tubulin abundance [ 181 ]. In preclinical models of osteosarcoma, microtubule-destabilizing agents increase cytoplasmic free tubulin causing a decrease of ΔΨ m [ 182 ].…”
Section: Mitochondria At the Crossroad Of Ferroptosis And Cancer Smentioning
confidence: 99%